IMPROVING READING COMPREHENSION OF THE EIGHTH GRADE STUDENTS THROUGH CONTEXT CLUES STRATEGY - Miftah Dewi Indriana; Aminah Aminah; Anjar Kusumua Dewi (Tadulako University, 2021)
The objective of this research is to find out whether the use of Context Clues strategy is effective to improve students’ reading comprehension. The population of this research was the eighth-grade students of SMPN 20 Sigi. The sample was selected by using a purposive sampling technique. There were two groups selected, i.e. class VIII B was the experimental group, and class VIII C was the control group. The data were obtained by using a test of reading comprehension. Both groups were asked to do the test twice as pre-test and post-test. The experimental group got the higher score than the control group after the treatment. To get the deviation score, the researchers calculated each student’s pre-test and post-test scores. From the result of the score deviation, the researchers calculated the mean deviation of both classes to get sum-square deviation score. Then, the researchers continued using the result to find out the tcounted using the ttest formula. After analyzing the data, the result showed that the tcounted (4.3) is higher than the ttable (1.686). It indicates that Context Clues strategy is effective to improve reading comprehension of the eighth grade students of SMPN 20 Sigi.